(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Chitra Banerjee Divakaruni is a remarkable diasporic writer who settled in America. She is from Bengal, India. She honours her Indian roots through her writings. Food items of Bengal is an intrinsic part of the Bengal’s indigenous culture. In her narrative, culinary elements hold a significant role. In her novels she gives enough references to the Bengali dishes which show her love for the flavours of Bengal. The presence of the authentic Bengal recipes is profusely seen in the corpus of her novels such as Queen of Dreams and Before We Visit the Goddess. She mentions specific dishes and ingredients to evoke the flavours, aromas and textures associated with Bengali cuisine.